2005
DOI: 10.1242/dev.01668
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inhalf baked/E-cadherin block cell behaviors that are necessary for teleost epiboly

Abstract: Epiboly, the spreading of the blastoderm over the large yolk cell, is the first morphogenetic movement of the teleost embryo. Examining this movement as a paradigm of vertebrate morphogenesis, we have focused on the epiboly arrest mutant half baked (hab), which segregates as a recessive lethal, including alleles expressing zygotic-maternal dominant (ZMD) effects. Here we show that hab is a mutation in the zebrafish homolog of the adhesion protein E-cadherin. Whereas exclusively recessive alleles of hab produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
226
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(254 citation statements)
references
References 51 publications
19
226
3
2
Order By: Relevance
“…This role may underlie their importance in early development, since presomitic mesoderm is surrounded by cadherins. Both zebrafish embryos deficient in E-cadherin (Cdh1, epithelial cadherin) by knockdown with morpholino RNAs (Babb and Marrs, 2004) and the homozygous half baked/Ecadherin mutant embryos (Kane et al, 2005) have mild to severe defects almost identical to those we observed with knockdown of p120 catenin d1 with the AUG start-site MOs (Supp. Fig.…”
Section: Developmental Dynamicssupporting
confidence: 61%
“…This role may underlie their importance in early development, since presomitic mesoderm is surrounded by cadherins. Both zebrafish embryos deficient in E-cadherin (Cdh1, epithelial cadherin) by knockdown with morpholino RNAs (Babb and Marrs, 2004) and the homozygous half baked/Ecadherin mutant embryos (Kane et al, 2005) have mild to severe defects almost identical to those we observed with knockdown of p120 catenin d1 with the AUG start-site MOs (Supp. Fig.…”
Section: Developmental Dynamicssupporting
confidence: 61%
“…In development, differential adhesion has been shown to play an important role in cell sorting (61)(62)(63), and the reorganization of intercellular forces in this context is entirely unexplored. Furthermore, in wound healing, we expect strong cell-ECM forces to be generated at a wound edge due to the local loss of intercellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Moreover, the knockdown of E-cadherin strongly affects early development in the zebrafish. 32 However, the knockdown of nrz does not seem to affect the expression of E-cadherin in the zebrafish gastrula (results not shown), whereas paraxial protocadherin, another adhesion molecule having a role during gastrulation, 33 is upregulated upon nrz knockdown (see Supplemental data S3). Thus, although the underlying molecular mechanisms remain to be determined, this report supports the idea that, during development, cell movements and adhesion may be controlled by Bcl-2 family members, at least in part via snail-dependent pathways, independently of apoptosis.…”
Section: Nrz Controls Gastrulation Via a Snail-1-dependent Pathwaymentioning
confidence: 92%